Distinct Genomic Features Characterize Two Clades of Corynebacterium diphtheriae: Proposal of Corynebacterium diphtheriae Subsp. diphtheriae Subsp. nov. and Corynebacterium diphtheriae Subsp. lausannense Subsp. nov. - Tagini, Florian; Pillonel, Trestan; Croxatto, Antony; Bertelli, Claire; Koutsokera, Angela; Lovis, Alban; Greub, Gilbert (Frontiers in Microbiology, 2018)
Corynebacterium diphtheriae is the etiological agent of diphtheria, a disease caused by the presence of the diphtheria toxin. However, an increasing number of records report non-toxigenic C. diphtheriae infections. Here, a C. diphtheriae strain was recovered from a patient with a past history of bronchiectasis who developed a severe tracheo-bronchitis with multiple whitish lesions of the distal trachea and the mainstem bronchi. Whole-genome sequencing (WGS), performed in parallel with PCR targeting the toxin gene and the Elek test, provided clinically relevant results in a short turnaround time, showing that the isolate was non-toxigenic. A comparative genomic analysis of the new strain (CHUV2995) with 56 other publicly available genomes of C. diphtheriae revealed that the strains CHUV2995, CCUG 5865 and CMCNS703 share a lower average nucleotide identity (ANI) (95.24 to 95.39%) with the C. diphtheriae NCTC 11397T reference genome than all other C. diphtheriae genomes (>98.15%). Core genome phylogeny confirmed the presence of two monophyletic clades. Based on these findings, we propose here two new C. diphtheriae subspecies to replace the lineage denomination used in previous multilocus sequence typing studies: C. diphtheriae subsp. lausannense subsp. nov. (instead of lineage-2), regrouping strains CHUV2995, CCUG 5865, and CMCNS703, and C. diphtheriae subsp. diphtheriae subsp. nov, regrouping all other C. diphtheriae in the dataset (instead of lineage-1). Interestingly, members of subspecies lausannense displayed a larger genome size than subspecies diphtheriae and were enriched in COG categories related to transport and metabolism of lipids (I) and inorganic ion (P). Conversely, they lacked all genes involved in the synthesis of pili (SpaA-type, SpaD-type and SpaH-type), molybdenum cofactor and of the nitrate reductase. Finally, the CHUV2995 genome is particularly enriched in mobility genes and harbors several prophages. The genome encodes a type II-C CRISPR-Cas locus with 2 spacers that lacks csn2 or cas4, which could hamper the acquisition of new spacers and render strain CHUV2995 more susceptible to bacteriophage infections and gene acquisition through various mechanisms of horizontal gene transfer.